Effects of conditioning on the left ventricular function of young purebred Arabian horses - Ramos, Gabriel Vieira [UNESP]; Santos, Maíra Moreira [UNESP]; Gava, Fábio Nelson; de Lacerda-Neto, José Corrêa [UNESP] (Public Library of Science (PLoS), 2024)
The effects of conditioning on cardiac function in young horses is still unknown. For this reason, this study evaluated the left ventricular (LV) function of young horses by echocardiography after six weeks of conditioning. Fourteen untrained young purebred Arabian horses were evaluated at rest and after a stress test (ST) before and after a six-week conditioning program. There was an increase in V4 (p < 0.001) after conditioning, as well as a reduction in both heart rate (HR) at rest and peak HR during the ST (p < 0.001). There was also a reduction in internal diameter, along with an increase in interventricular septal, free wall and mean thicknesses and LV mass (p < 0.05). After the ST, the conditioned animals showed higher values of velocity time integral, stroke volume, systolic and cardiac indices, ejection (ET) and deceleration times (DT), end-diastolic volume, time to onset of radial myocardial velocity during early diastole and time to peak of transmitral flow velocity, in addition to reduced pre-ejection period (PEP), PEP/ET ratio and mean velocity of circumferential fiber shortening (p < 0.05). The conditioning protocol promoted physiological adaptations that indicate an improvement in the animals’ aerobic capacity associated with an enhanced left ventricular function.